Bacteroides thetaiotaomicron Fosters the Growth of Butyrate-Producing Anaerostipes caccae in the Presence of Lactose and Total Human Milk Carbohydrates - Loo Wee Chia; Marko Mank; Bernadet Blijenberg; Steven Aalvink; Roger S. Bongers; Bernd Stahl; Jan Knol; Clara Belzer (Microorganisms, 2020)
The development of infant gut microbiota is strongly influenced by nutrition. Human milk oligosaccharides (HMOSs) in breast milk selectively promote the growth of glycan-degrading microbes, which lays the basis of the microbial network. In this study, we investigated the trophic interaction between Bacteroides thetaiotaomicron and the butyrate-producing Anaerostipes caccae in the presence of early-life carbohydrates. Anaerobic bioreactors were set up to study the monocultures of B. thetaiotaomicron and the co-cultures of B. thetaiotaomicron with A. caccae in minimal media supplemented with lactose or a total human milk carbohydrate fraction. Bacterial growth (qPCR), metabolites (HPLC), and HMOS utilization (LC-ESI-MS2) were monitored. B. thetaiotaomicron displayed potent glycan catabolic capability with differential preference in degrading specific low molecular weight HMOSs, including the neutral trioses (2′-FL and 3-FL), neutral tetraoses (DFL, LNT, LNnT), neutral pentaoses (LNFP I, II, III, V), and acidic trioses (3′-SL and 6′-SL). In contrast, A. caccae was not able to utilize lactose and HMOSs. However, the signature metabolite of A. caccae, butyrate, was detected in co-culture with B. thetaiotaomicron. As such, A. caccae cross-fed on B. thetaiotaomicron-derived monosaccharides, acetate, and d-lactate for growth and concomitant butyrate production. This study provides a proof of concept that B. thetaiotaomicron could drive the butyrogenic metabolic network in the infant gut.